Nano-imprinting ultraviolet curing glue with high refractive index and preparation method thereof

By using high-refractive index nanoimprinting ultraviolet curing glue in the diffraction light waveguide nanoimprinting process, the problem of low refractive index of product glue is solved, and the refractive index reaches more than 2.0, improving the light efficiency and contrast.

CN119463712APending Publication Date: 2025-02-18ZHEJIANG ZHIGE TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411593300.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the prior art, the refractive index of the product used in the nanoimprinting process of diffraction optical waveguide is less than 2.0, which cannot meet the requirements of the refractive index consistency of the glass wafer, resulting in a large reflection effect of the diffraction optical waveguide at the interface. Ineffective.

Method used

Provide a high-refractive index nanoimprinted ultraviolet curing glue containing modified titanium oxide nanoparticles, monofunctional monomers and multifunctional monomers. By adjusting component ratios and selecting appropriate photoinitiators and leveling additives , ensure that the refractive index of the glue reaches above 2.0 after ultraviolet light exposure and high temperature baking.

Benefits of technology

The refractive index of diffraction optical waveguide product glue reaches above 2.0, reduces the interface reflection effect, improves the light effect and contrast, and ensures the good fluidity and transfer ability of the glue.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005126143470000121
    Figure BDA0005126143470000121
Patent Text Reader

Abstract

The invention provides nano-imprinting ultraviolet curing glue with high refractive index and a preparation method of the nano-imprinting ultraviolet curing glue, and the ultraviolet curing glue comprises the following components in percentage by mass: 70-95% of modified titanium oxide nanoparticles, 1-25% of a monofunctional monomer and 0.5-10% of a polyfunctional monomer. Wherein the refractive index of the modified titanium oxide nanoparticles is 2.0 or above, and the monofunctional monomer and the polyfunctional monomer adopt an acrylate monomer containing a naphthalene ring structure or an acrylate monomer with a benzene ring structure and a sulfur element at the same time. In the nanoimprint process of the diffraction optical waveguide, the refractive index of the ultraviolet curing glue is close to 2.0 after the ultraviolet curing glue is cured under ultraviolet irradiation, the refractive index of the ultraviolet curing glue can reach 2.0 or above after a diffraction optical waveguide product with a grating structure obtained through demolding is baked at high temperature, meanwhile, the glue has good flowability, and the ultraviolet curing glue can be applied to the nanoimprint process of the diffraction optical waveguide. And the grating structure can be normally transferred.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of diffraction optical waveguide preparation, and in particular relates to a high-refractive-index nanoimprint ultraviolet light-curing glue and a preparation method thereof. Background Art

[0002] The existing method for preparing diffractive optical waveguides is generally:

[0003] 1. Prepare an imprint master with a preset grating structure.

[0004] 2. The grating structure of the imprint master is transferred to the soft film through the nanoimprint process to obtain the inverse structure of the grating structure on the soft film.

[0005] Specifically, the embossing glue is evenly spin-coated on the embossing master, the soft film substrate is bonded to the embossing master, pressure is applied to fill the embossing glue into the grating structure of the embossing master, and the inverse structure of the grating structure is obtained on the embossing glue. The embossing glue with the inverse structure of the grating structure is transferred to the soft film substrate by ultraviolet light curing and demolding, so as to obtain a soft film with the inverse structure of the grating structure.

[0006] 3. The inverse structure of the grating structure on the soft film is transferred to the glass wafer through the nanoimprint process to obtain a glass wafer with a grating structure, thereby obtaining a diffraction optical waveguide.

[0007] Specifically, a tackifier and a product glue are spin-coated on a glass wafer in sequence, a soft film with a grating structure inverse structure is bonded to the product glue on the glass wafer, pressure is applied to allow the product glue to fill the grating structure inverse structure of the soft film, a grating structure is obtained on the product glue, ultraviolet light is used for curing and demolding, the soft film with a grating structure inverse structure is separated from the product glue with a grating structure, a glass wafer with a grating structure is obtained, and thus a diffraction optical waveguide is obtained.

[0008] Since the grating structure of the diffraction waveguide is imprinted on the product glue of the diffraction waveguide, the refractive index of the product glue needs to be consistent with the refractive index of the glass wafer. Keeping the refractive index of the product glue consistent with the refractive index of the glass wafer has the following beneficial effects: reducing the reflection effect of the diffraction waveguide at the interface, improving the contrast of the image coupled out of the diffraction waveguide and the optical effect (the ratio of the average brightness of the virtual image displayed by the module composed of the diffraction waveguide and the micro-projector to the luminous flux emitted by the micro-projector) and other optical properties.

[0009] The refractive index of existing glass wafers has reached above 2.0, but the refractive index of the product glue used for the diffraction optical waveguide nanoimprint process is below 2.0. Therefore, how to improve the refractive index of the product glue used for the diffraction optical waveguide nanoimprint process to not less than 2.0 is an urgent problem to be solved in this field. Summary of the invention

[0010] In order to overcome the defects of the prior art, the present invention provides a high refractive index nanoimprint UV-curing glue and a preparation method thereof.

[0011] The present invention is achieved through the following technical solutions:

[0012] The present invention provides a high refractive index nanoimprint UV curing glue, which comprises the following components by mass percentage:

[0013] Modified titanium oxide nanoparticles 70-95%;

[0014] Monofunctional monomer 1-25%;

[0015] Multifunctional monomer 0.5-10%;

[0016] Wherein, the refractive index of the modified titanium oxide nanoparticles is above 2.0;

[0017] The monofunctional monomer and the multifunctional monomer are acrylic acid ester monomers containing a naphthalene ring structure or acrylic acid ester monomers having both a benzene ring structure and a sulfur element.

[0018] Furthermore, the following components are included by mass percentage:

[0019] Modified titanium oxide nanoparticles 75-90%;

[0020] Monofunctional monomer 10-20%;

[0021] Multifunctional monomer 0.5-5%.

[0022] The modified titanium oxide nanoparticles can be obtained from a modified titanium oxide nanoparticle dispersion. The modified titanium oxide nanoparticle dispersion can be produced by Nissan Chemical Co., Ltd., and the product model is OT-RB200P7-EX205 (the content of modified titanium oxide nanoparticles is 20%).

[0023] Furthermore, the monofunctional monomer is one of 2-naphthyl acrylate, 2-naphthylmethyl acrylate and 2-phenylthioethanol acrylate.

[0024] Furthermore, the multifunctional monomer is one of 4,4'-dimercaptodiphenyl sulfide dimethyl methacrylate and triphenyl isocyanate triacrylate.

[0025] Furthermore, by weight percentage, it also includes:

[0026] Cleavage type photoinitiator 0.5-10%.

[0027] Furthermore, the cleavage-type photoinitiator is selected from one of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide and 1-hydroxycyclohexylphenyl ketone.

[0028] Furthermore, by weight percentage, it also includes:

[0029] Leveling agent 0.05-10%;

[0030] The leveling agent is preferably one of BYK310 leveling agent, BYK378 leveling agent and BYK354 leveling agent produced by BYK Chemical.

[0031] The present invention also provides a method for preparing the above-mentioned high refractive index nanoimprint UV-curing glue, comprising the following steps:

[0032] Weighing the modified titanium oxide nanoparticles, the monofunctional monomer, and the multifunctional monomer according to the mass percentage;

[0033] The monofunctional monomer and the multifunctional monomer are stirred and mixed evenly, and then the modified titanium oxide nanoparticles are added and stirred and mixed evenly to obtain a high refractive index nanoimprint ultraviolet light curing glue.

[0034] Furthermore, it also includes:

[0035] Weigh the cleavage type photoinitiator by mass percentage, 0.5-10% of the cleavage type photoinitiator;

[0036] The monofunctional monomer, the multifunctional monomer and the cleavage-type photoinitiator are stirred and mixed evenly, and then the modified titanium oxide nanoparticles are added and stirred and mixed evenly to obtain a high refractive index nanoimprint ultraviolet light curing glue.

[0037] Furthermore, it also includes:

[0038] Weigh the leveling agent by mass percentage, 0.05-10% of the leveling agent;

[0039] The monofunctional monomer, the multifunctional monomer, the cleavage-type photoinitiator and the leveling aid are stirred and mixed evenly, and then the modified titanium oxide nanoparticles are added and stirred and mixed evenly to obtain a high refractive index nanoimprint ultraviolet light curing glue.

[0040] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0041] The invention provides a high refractive index nano-imprint UV-curing glue, which comprises the following components by mass percentage: 70-95% of modified titanium oxide nanoparticles, 1-25% of monofunctional monomers, and 0.5-10% of multifunctional monomers. The refractive index of the modified titanium oxide nanoparticles is above 2.0, and the monofunctional monomers and multifunctional monomers are acrylic acid ester monomers containing a naphthalene ring structure or acrylic acid ester monomers having both a benzene ring structure and sulfur elements. By adjusting the component ratio of modified titanium oxide nanoparticles, monofunctional monomers and multifunctional monomers, the refractive index of the selected modified titanium oxide nanoparticles is controlled to be above 2.0, and the monofunctional monomers and multifunctional monomers are acrylate monomers containing a naphthalene ring structure or acrylate monomers having a benzene ring structure and a sulfur element. In the nanoimprint process of the diffraction optical waveguide, the UV-curable glue provided by the present invention has a refractive index close to 2.0 after being cured by UV light, and the refractive index of the UV-curable glue can reach above 2.0 after the diffraction optical waveguide product with a grating structure obtained by demolding is baked at high temperature. At the same time, the glue has good fluidity and can transfer the grating structure normally.

[0042] The high refractive index nanoimprint UV-curing glue provided by the present invention adopts a cleavage-type photoinitiator. After the diffractive optical waveguide product with a grating structure is baked at high temperature after demolding in the nanoimprint process of the diffractive optical waveguide, the refractive index of the UV-curing glue can be greatly improved. DETAILED DESCRIPTION

[0043] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] In this article, the terms "first", "second" and other similar words are not intended to imply any order, quantity and importance, but are only used to distinguish different elements. In this article, the terms "one", "an" and other similar words are not intended to indicate that there is only one of the things described, but rather indicate that the relevant description is only for one of the things described, and the things described may have one or more. In this article, the terms "comprise", "include" and other similar words are intended to indicate logical mutual relationships, and cannot be regarded as indicating spatial structural relationships. For example, "A includes B" is intended to indicate that B belongs to A logically, but does not indicate that B is located inside A spatially. In addition, the meanings of the terms "comprise", "include" and other similar words should be regarded as open, rather than closed. For example, "A includes B" is intended to indicate that B belongs to A, but B does not necessarily constitute the whole of A, and A may also include other elements such as C, D, and E.

[0045] In this document, the terms "embodiment", "present embodiment", "preferred embodiment", and "one embodiment" do not mean that the relevant description is only applicable to a specific embodiment, but rather that the description may also be applicable to one or more other embodiments. Those skilled in the art should understand that in this document, any description of a certain embodiment can be replaced, combined, or combined in other ways with the relevant description in one or more other embodiments, and the new embodiment generated by the replacement, combination, or combination in other ways is easily conceivable by those skilled in the art and falls within the scope of protection of the present invention.

[0046] In the description herein, “plurality” means at least two, for example, two, three, etc., unless otherwise clearly and specifically defined.

[0047] Example 1

[0048] The high refractive index nanoimprint UV curing glue of this embodiment is composed of the following components by mass:

[0049] 2-Naphthyl acrylate (NTA): 12 g;

[0050] 4,4'-dimercaptodiphenyl sulfide dimethyl methacrylate (BMTPS): 3g;

[0051] 2-Hydroxy-2-methyl-1-phenyl-1-propanone: 2.5 g;

[0052] Leveling agent (produced by BYK Chemical, product model: BYK310): 0.5g;

[0053] Modified titanium oxide nanoparticle dispersion (produced by Nissan Chemical Co., Ltd., product model: OT-RB200P7-EX205): 410 g.

[0054] The method for preparing the high refractive index nanoimprint UV-curable glue of this embodiment comprises the following steps:

[0055] 2-Naphthyl acrylate (NTA), 4,4'-dimercaptodiphenyl sulfide dimethyl methacrylate (BMTPS), 2-hydroxy-2-methyl-1-phenyl-1-propanone, leveling agent (produced by BYK Chemical, product model: BYK310) and modified titanium oxide nanoparticle dispersion (produced by Nissan Chemical Co., Ltd., product model: OT-RB200P7-EX205) were weighed according to the above masses.

[0056] The above-mentioned mass of 2-naphthyl acrylate (NTA), 4,4'-dimercaptodiphenyl sulfide dimethyl methacrylate (BMTPS), 2-hydroxy-2-methyl-1-phenyl-1-propanone, and leveling agent (produced by BYK Chemical, product model: BYK310) are stirred evenly, and then the above-mentioned mass of modified titanium oxide nanoparticle dispersion (produced by Nissan Chemical Co., Ltd., product model: OT-RB200P7-EX205) is added, and the mixture is accelerated and stirred at 2000 rpm in a centrifugal mixer for 3 minutes to obtain a high refractive index nanoimprint UV-curing glue.

[0057] Example 2

[0058] The high refractive index nanoimprint UV curing glue of this embodiment is composed of the following components by mass:

[0059] 2-Naphthyl methyl acrylate: 14.5 g;

[0060] Thiophosphoric acid triphenyl isocyanate triacrylate: 0.5 g;

[0061] 2,4,6-Trimethylbenzoyldiphenylphosphine oxide: 2.5 g;

[0062] Leveling agent (produced by BYK Chemical, product model: BYK378) 0.5g;

[0063] Modified titanium oxide nanoparticle dispersion (produced by Nissan Chemical Co., Ltd., product model: OT-RB200P7-EX205): 410 g.

[0064] The method for preparing the high refractive index nanoimprint UV-curable glue of this embodiment comprises the following steps:

[0065] 2-naphthylmethyl acrylate, triphenyl isocyanate triacrylate, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, a leveling agent (produced by BYK Chemical, product model: BYK378) and a modified titanium oxide nanoparticle dispersion (produced by Nissan Chemical Co., Ltd., product model: OT-RB200P7-EX205) were weighed according to the above masses.

[0066] The above-mentioned mass of 2-naphthyl methyl acrylate, triphenyl isocyanate triacrylate, 2,4,6-trimethylbenzoyl diphenyl phosphine oxide, and leveling agent (produced by BYK Chemical, product model: BYK378) are stirred evenly, and then the above-mentioned mass of modified titanium oxide nanoparticle dispersion (produced by Nissan Chemical Co., Ltd., product model: OT-RB200P7-EX205) is added, and the mixture is accelerated and stirred at 2000 rpm in a centrifugal mixer for 3 minutes to obtain a high refractive index nanoimprint UV-curing glue.

[0067] Comparative Example 1

[0068] The nanoimprint UV curing glue of this comparative example is composed of the following components by mass:

[0069] 4,4'-dimercaptodiphenyl sulfide dimethyl methacrylate: 15g;

[0070] 2-Hydroxy-2-methyl-1-phenyl-1-propanone: 2.5 g;

[0071] Leveling agent (produced by BYK Chemical, product model: BYK310) 0.5g;

[0072] Modified titanium oxide nanoparticle dispersion (produced by Nissan Chemical Co., Ltd., product model: OT-RB200P7-EX205): 410 g.

[0073] The method for preparing the nanoimprint UV-curable glue of this embodiment comprises the following steps:

[0074] 4,4'-dimercaptodiphenyl sulfide dimethacrylate, 2-hydroxy-2-methyl-1-phenyl-1-propanone, a leveling agent (produced by BYK Chemical, product model: BYK378) and a modified titanium oxide nanoparticle dispersion (produced by Nissan Chemical Co., Ltd., product model: OT-RB200P7-EX205) were weighed according to the above masses.

[0075] The above-mentioned mass of 4,4'-dimercaptodiphenyl sulfide dimethacrylate, 2-hydroxy-2-methyl-1-phenyl-1-propanone, and leveling agent (produced by BYK Chemical, product model: BYK378) were stirred evenly, and then the above-mentioned mass of modified titanium oxide nanoparticle dispersion (produced by Nissan Chemical Co., Ltd., product model: OT-RB200P7-EX205) was added, and the mixture was accelerated and stirred at 2000 rpm in a centrifugal mixer for 3 minutes to obtain nanoimprint UV-curing glue.

[0076] Comparative Example 2

[0077] The nanoimprint UV curing glue of this comparative example is composed of the following components by mass:

[0078] 2-Naphthyl acrylate (NTA): 12 g;

[0079] 4,4'-dimercaptodiphenyl sulfide dimethyl methacrylate (BMTPS): 3g;

[0080] Methyl benzoylformate (MBF): 2.5 g;

[0081] Leveling agent (produced by BYK Chemical, product model: BYK310): 0.5g;

[0082] Modified titanium oxide nanoparticle dispersion (produced by Nissan Chemical Co., Ltd., product model: OT-RB200P7-EX205): 410 g.

[0083] The preparation method of the nanoimprint UV-curable glue of this comparative example comprises the following steps:

[0084] 2-Naphthyl acrylate (NTA), 4,4'-dimercaptodiphenyl sulfide dimethyl methacrylate (BMTPS), methyl benzoylformate (MBF), a leveling agent (produced by BYK Chemical, product model: BYK310) and a modified titanium oxide nanoparticle dispersion were weighed according to the above masses.

[0085] The above-mentioned mass of 2-naphthyl acrylate (NTA), 4,4'-dimercaptodiphenyl sulfide dimethyl methacrylate (BMTPS), methyl benzoylformate (MBF), and leveling agent (produced by BYK Chemical, product model: BYK310) are stirred evenly, and then the above-mentioned mass of modified titanium oxide nanoparticle dispersion (produced by Nissan Chemical Co., Ltd., product model: OT-RB200P7-EX205) is added, and the mixture is accelerated and stirred at 2000 rpm in a centrifugal mixer for 3 minutes to obtain nanoimprint UV-curing glue.

[0086] Comparative Example 3

[0087] The nanoimprint UV curing glue of this comparative example is composed of the following components by mass:

[0088] 2-Naphthyl acrylate (NTA): 12 g;

[0089] 4,4'-dimercaptodiphenyl sulfide dimethyl methacrylate (BMTPS): 3g;

[0090] 2-Hydroxy-2-methyl-1-phenyl-1-propanone: 2.5 g;

[0091] Leveling agent (produced by BYK Chemical, product model: BYK310): 0.5g;

[0092] Titanium oxide dispersion (produced by Mikoku Pigments Co., Ltd., product model: MHIFILLER#FM-884M, titanium oxide particle content 45%): 182.2 g;

[0093] The preparation method of the nanoimprint UV-curable glue of this comparative example comprises the following steps:

[0094] 2-naphthyl acrylate (NTA), 4,4'-dimercaptodiphenyl sulfide dimethacrylate (BMTPS), 2-hydroxy-2-methyl-1-phenyl-1-propanone, leveling agent (produced by BYK Chemical, product model: BYK310) and titanium oxide dispersion (produced by Mikoku Pigments Co., Ltd., product model: MHIFILLER#FM-884M) were weighed according to the above masses.

[0095] The above-mentioned mass of 2-naphthyl acrylate (NTA), 4,4'-dimercaptodiphenyl sulfide dimethyl methacrylate (BMTPS), 2-hydroxy-2-methyl-1-phenyl-1-propanone, and leveling agent (produced by BYK Chemical, product model: BYK310) are stirred evenly, and then the above-mentioned mass of titanium oxide dispersion (produced by Mikoku Pigments Co., Ltd., product model: MH IF ILLER#FM-884M) is added, and the mixture is accelerated and stirred at 2000 rpm in a centrifugal mixer for 3 minutes to obtain nanoimprint UV-curing glue.

[0096] Comparative Example 4

[0097] The nanoimprint UV curing glue of this comparative example is composed of the following components by mass:

[0098] o-phenylphenoxyethyl acrylate (OPPEA): 7.5 g;

[0099] Bisphenol A diglycidyl ether dimethacrylate (BPA): 7.5g;

[0100] 2-Hydroxy-2-methyl-1-phenyl-1-propanone: 2.5 g;

[0101] Leveling agent (produced by BYK Chemical, product model: BYK310): 0.5g;

[0102] Modified titanium oxide nanoparticle dispersion (produced by Nissan Chemical Co., Ltd., product model: OT-RB200P7-EX205): 410 g.

[0103] The preparation method of the nanoimprint UV-curable glue of this comparative example comprises the following steps:

[0104] According to the above mass, o-phenylphenoxyethyl acrylate (OPPEA), bisphenol A diglycidyl ether dimethacrylate (BPA), 2-hydroxy-2-methyl-1-phenyl-1-propanone, leveling agent (produced by BYK Chemical, product model: BYK310) and modified titanium oxide nanoparticle dispersion (produced by Nissan Chemical Co., Ltd., product model: OT-RB200P7-EX205) were weighed respectively.

[0105] The above-mentioned mass of o-phenylphenoxyethyl acrylate (OPPEA), bisphenol A diglycidyl ether dimethacrylate (BPA), 2-hydroxy-2-methyl-1-phenyl-1-propanone, and leveling agent (produced by BYK Chemical, product model: BYK310) are stirred evenly, and then the above-mentioned mass of modified titanium oxide nanoparticle dispersion (produced by Nissan Chemical Co., Ltd., product model: OT-RB200P7-EX205) is added, and the mixture is accelerated and stirred at 2000 rpm in a centrifugal mixer for 3 minutes to obtain a high refractive index nanoimprint UV-curing glue.

[0106] The nanoimprint process of applying the UV-curable glue of the above-mentioned Examples 1-2 and Comparative Examples 1-4 to the diffractive optical waveguide is as follows:

[0107] 1. Prepare an imprint master with a preset grating structure.

[0108] 2. Transfer the grating structure of the imprint master to the soft film through the nanoimprint process to obtain the inverse structure of the grating structure on the soft film;

[0109] Specifically,

[0110] The imprint glue is evenly spin-coated on the imprint master, the soft film substrate is bonded to the imprint master, and pressure is applied to fill the imprint glue into the grating structure of the imprint master, and the inverse structure of the grating structure is obtained on the imprint glue. The imprint glue with the inverse structure of the grating structure is transferred to the soft film substrate by ultraviolet light curing and demolding, and a soft film with the inverse structure of the grating structure is obtained.

[0111] 3. The inverse structure of the grating structure on the soft film is transferred to the waveguide substrate through a nanoimprint process to obtain a waveguide substrate with a grating structure, thereby obtaining a diffraction optical waveguide.

[0112] Specifically,

[0113] A glass wafer (i.e., a waveguide substrate) with a surface subjected to adhesion enhancement treatment is placed on a glue spreader, and the UV-curable glues of the above-mentioned embodiments 1-2 and comparative examples 1-4 are respectively added and spin-coated to obtain a uniform glue film layer with a nanometer-level thickness; a soft film with a grating structure inverse structure is pressed onto the glue film layer to obtain a grating structure on the glue film layer; then, an ultraviolet light source is irradiated to solidify the glue film layer with the grating structure, and then the soft film with the grating structure inverse structure is separated from the glue film layer with the grating structure, and demolding is completed to obtain a diffraction optical waveguide product with a grating structure, and then baked at a high temperature of 150° C. for 20 minutes to obtain a final diffraction optical waveguide product.

[0114] The performance tests of the UV-curable glues of the above-mentioned Examples 1-2 and Comparative Examples 1-4 in the diffraction optical waveguide nanoimprinting process are as follows:

[0115] Refractive index test: Use an ellipsometer to test the refractive index of the adhesive layer to obtain the refractive index of the adhesive layer at a wavelength of 532nm (it should be noted that the wavelength of 532nm is only an example, and other wavelengths can also be used).

[0116] Structural transfer rate test: Use a scanning electron microscope (SEM) or an atomic force microscope (AFM) to measure the size (height and width) of the nanostructure (i.e., grating structure) of the diffraction optical waveguide product, and compare it with the size (height and width) of the sub-template (the anti-structure of the grating structure on the soft film) to obtain the corresponding structural transfer rate.

[0117] The test results are shown in Table 1:

[0118] Table 1:

[0119]

[0120] By comparing the test results of Examples 1-2 in the above table, it can be seen that in the nanoimprint process of the diffraction optical waveguide, the refractive index of the UV-curable glue provided by the present invention is close to 2.0 after UV-light irradiation and curing, and the refractive index of the UV-curable glue can reach above 2.0 after the diffraction optical waveguide product with a grating structure is demolded and baked at high temperature. At the same time, the glue has good fluidity and can transfer the grating structure normally.

[0121] By comparing Example 1 and Comparative Example 1, it can be seen that in the nanoimprint process of the diffractive optical waveguide, the component ratio of the multifunctional monomer in the UV-curable glue is reduced, and after the diffractive optical waveguide product with a grating structure after demolding is baked at high temperature, the refractive index of the UV-curable glue is greatly improved, and the refractive index of the UV-curable glue is greater than 2.0.

[0122] By comparing Example 1 and Comparative Example 2, it can be seen that in the nanoimprint process of the diffraction optical waveguide, compared with the use of Type II initiator (methyl benzoylformate), the use of Type I photoinitiator (i.e., cleavage-type photoinitiator, 2-hydroxy-2-methyl-1-phenyl-1-propanone) can greatly improve the refractive index of the UV-curable glue after the diffraction optical waveguide product with a grating structure after demolding is baked at high temperature, and the refractive index of the UV-curable glue is greater than 2.0.

[0123] By comparing Example 1 and Comparative Example 3, it can be seen that different titanium oxide particle dispersions have different structural transfer abilities. The modified titanium oxide nanoparticle dispersion of the present invention can not only improve the refractive index of the UV-curable glue, but also improve the fluidity of the glue and the high transfer ability.

[0124] By comparing Example 1 and Comparative Example 4, it can be seen that the monofunctional monomer and the multifunctional monomer using an acrylate monomer containing a naphthalene ring structure or an acrylate monomer having both a benzene ring structure and a sulfur element can effectively increase the refractive index of the UV-curable glue.

[0125] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the same. Although the present invention has been described in detail with reference to the above embodiments, a person skilled in the art can still modify or make equivalent substitutions to the specific implementations of the present invention. Any modifications or equivalent substitutions that do not depart from the spirit and scope of the present invention are within the scope of protection of the claims of the present invention to be approved.

Claims

1. A high refractive index nanoimprint UV curing glue, characterized in that: Calculated by mass percentage, it includes the following components: Modified titanium oxide nanoparticles 70-95%; Monofunctional monomer 1-25%; Multifunctional monomer 0.5-10%; Wherein, the refractive index of the modified titanium oxide nanoparticles is above 2.0; The monofunctional monomer and the multifunctional monomer are acrylic acid ester monomers containing a naphthalene ring structure or acrylic acid ester monomers having both a benzene ring structure and a sulfur element.

2. The high refractive index nanoimprint UV curing glue according to claim 1, characterized in that: Calculated by mass percentage, it includes the following components: Modified titanium oxide nanoparticles 75-90%; Monofunctional monomer 10-20%; Multifunctional monomer 0.5-5%.

3. The high refractive index nanoimprint UV curing glue according to claim 1, characterized in that: The monofunctional monomer is one of 2-naphthyl acrylate, 2-naphthyl methyl acrylate and 2-phenylthioethanol acrylate.

4. The high refractive index nanoimprint UV curing glue according to claim 1, characterized in that: The multifunctional monomer is one of 4,4'-dimercaptodiphenyl sulfide dimethyl methacrylate and triphenyl isocyanate triacrylate.

5. The high refractive index nanoimprint UV curing glue according to claim 1, characterized in that: In terms of mass percentage, it also includes: Cleavage type photoinitiator 0.5-10%.

6. The high refractive index nanoimprint UV curing glue according to claim 5, characterized in that: The cleavage-type photoinitiator is selected from one of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide and 1-hydroxycyclohexylphenyl ketone.

7. The high refractive index nanoimprint UV curing glue according to claim 1, characterized in that: In terms of mass percentage, it also includes: Leveling agent 0.05-10%; The leveling agent is one of BYK310 leveling agent, BYK378 leveling agent and BYK354 leveling agent.

8. The method for preparing the high refractive index nanoimprint UV-curing glue according to any one of claims 1 to 4, characterized in that: The steps include: Weighing the modified titanium oxide nanoparticles, the monofunctional monomer, and the multifunctional monomer according to the mass percentage; The monofunctional monomer and the multifunctional monomer are stirred and mixed evenly, and then the modified titanium oxide nanoparticles are added and stirred and mixed evenly to obtain a high refractive index nanoimprint ultraviolet light curing glue.

9. The method for preparing a high refractive index nanoimprint UV-curable glue according to claim 8, characterized in that: Also includes: Weigh the cleavage type photoinitiator by mass percentage, 0.5-10% of the cleavage type photoinitiator; The monofunctional monomer, the multifunctional monomer and the cleavage-type photoinitiator are stirred and mixed evenly, and then the modified titanium oxide nanoparticles are added and stirred and mixed evenly to obtain a high refractive index nanoimprint ultraviolet light curing glue.

10. The method for preparing a high refractive index nanoimprint UV-curable glue according to claim 8, characterized in that: Also includes: Weigh the leveling agent by mass percentage, 0.05-10% of the leveling agent; The monofunctional monomer, the multifunctional monomer, the cleavage-type photoinitiator and the leveling agent are stirred and mixed evenly, and then the modified titanium oxide nanoparticles are added and stirred and mixed evenly to obtain a high refractive index nanoimprint ultraviolet light curing glue.

Citation Information

Cited By

  • High-refractive-index high-temperature-resistant epoxy acrylic photo-thermal curing composition

    CN120623948A